Original Short Stories $1 (BVolume 03s - Maupassant, Guy de, 1850-1893; Henderson, A. E.; McMaster, Albert Cohn; Quesada, Louise Charlotte Garstin (Salt Lake City, UT : Project Gutenberg, 2004)
"Original Short Stories $1 (BVolume 03" by Guy de Maupassant is a collection of short stories published during the late 19th century, showcasing Maupassant's keen observation of human psychology and societal norms. In this volume, readers are likely to encounter a diverse array of characters and situations, exploring themes of love, loss, morality, and existential despair, particularly evident through the stories that include "Miss Harriet" and "Little Louise Roque". At the start of "Miss Harriet," a group of travelers embarks on a scenic journey from Etretat to visit Tancarville, setting the stage for the introduction of intriguing characters, such as the painter Leon Chenal and the eccentric Englishwoman, Miss Harriet. The narrative reveals Chenal's fascination with nature and art, while also hinting at a longing for deeper connection amidst a backdrop of social interactions that range from playful banter to underlying personal struggles. In contrast, "Little Louise Roque" opens with the discovery of a young girl's lifeless body in a forest, immediately plunging readers into a dark examination of crime, internal conflict, and the search for justice in a rural setting. The contrasting tones of innocence and suffering in these opening chapters establish a rich groundwork for Maupassant$1 (Bs explorations into the complexities of human experience. (This is an automatically generated summary.)s
Miss Harriet -- Little Louise Roque -- The donkey -- Moiron -- The dispenser of holy water -- The parricide -- Bertha -- The patron -- The door -- A sale -- The impolite sex -- A wedding gift -- The relic.
Release date is 2004-10-03
Produced by David Widger
Keywords: Short stories, French -- Translations into English